2020
DOI: 10.1021/acs.jpcb.9b10802
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Nanosecond Relaxation Dynamics of Rhenium-Labeled Pseudomonas aeruginosa Azurins

Abstract: Time-resolved phosphorescence spectra of Re(CO) 3 (dmp) + and Re(CO) 3 (phen) + chromophores (dmp = 4,7-dimethyl-1,10-phenanthroline, phen = 1,10-phenanthroline) bound to surface histidines (H83, H124, H126) of Pseudomonas aeruginosa azurin mutants exhibit dynamic band maxima shifts to lower wavenumbers following 3-exponential kinetics with 1-5 and 20-100 ns major phases, and a 1.1-2.5 s minor (5-16%) phase. Observation of slow relaxation components was made possible by using an organometallic Re chromophore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Changes of oscillator strength in the course of excited-state relaxation likely is a general effect that can extend to pico- and nanosecond time domains in slow-relaxing complex media such as ionic liquids or proteins. 82–84 Results of our nonadiabatic simulations also qualitatively match femtosecond evolution of Raman features observed in Rebpy FSRS spectra, 75 that are now attributable to the initial restructuring during the “slow” ISC phase.…”
Section: Discussionsupporting
confidence: 68%
“…Changes of oscillator strength in the course of excited-state relaxation likely is a general effect that can extend to pico- and nanosecond time domains in slow-relaxing complex media such as ionic liquids or proteins. 82–84 Results of our nonadiabatic simulations also qualitatively match femtosecond evolution of Raman features observed in Rebpy FSRS spectra, 75 that are now attributable to the initial restructuring during the “slow” ISC phase.…”
Section: Discussionsupporting
confidence: 68%
“…This barrier leads to an adiabatic reaction rate of ν N × 1.2 × 10 –3 s –1 , where ν N is the effective frequency of motion along the reaction coordinate. Dynamic phosphorescence and infrared absorption Stokes shift studies of various Re-labeled azurins revealed multiexponential solvation and protein relaxation dynamics ranging from picoseconds to tens of nanoseconds (plus a low-amplitude μs component). , Although not all these motions need to be coupled to ET, ν N can be safely estimated to be less than (100 ps) −1 , predicting ET to be slower than 83 ns, contrary to experiment (ca. 8 ns, likely faster for ″ in ″-CS1).…”
Section: Discussionmentioning
confidence: 94%
“…(For example, with H ab = 40 meV and λ = 800 meV, the Landau–Zener parameter 2πγ = π 3/2 < H ab 2 >/ h ν eff √(λ k B T ) equals 1 for ν eff = 1.5 × 10 13 s –1 (66 fs) –1 . Protein and solvent motions in Re-labeled azurins are orders of magnitude slower, , affording 2πγ ≫ 1, ensuring adiabaticity. , )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Slower phosphorescence than IR dynamic shifts also was observed for organometallic probes covalently appended to proteins. 46,49 ■ CONCLUSIONS Near-UV excitation of Prodan and Badan dyes in nonpolar (hexane) as well as polar (MeOH, glycerol) solvents produces an S 1 excited state of a ππ* character. In polar/H-bonding, the optically prepared S 1 (ππ*) state undergoes a solvent-driven intramolecular electron-density redistribution from NMe 2 to the CO group accompanied by lowering the S 1 excited-state energy.…”
Section: ■ Results and Discussionmentioning
confidence: 99%